Development of Primary Nursing Practice Model in Elisabet's Roomimmanuel Hospital Bandung - Liana Ginting; Mona Rentauli; Herwinda Sinaga; Lidya Maryani; Dalia Novitasari (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The Professional Nursing Practice Model (MPKP) is a model of providing nursing care that provides professional nurses with the opportunity to determine their autonomy in planning, implementing and evaluating nursing care to clients. This study was conducted to see the development of the primary nursing practice model in the inpatient Elizabeth Room of Immanuel Hospital. Pre-experimental research with one group control design, through the application of pre-test post-test in one group. The results of this study indicate an increase in knowledge after the implementation of the primary nursing practice model. Before the implementation of the model, most nurses obtained scores that tended to be in the middle category, with only a few achieving the highest scores with 4 primary nurses getting a minimum score of 7 (70%). After the implementation of the model, the increase in scores appeared more evenly distributed, with more nurses achieving optimal scores with 2 nurses getting a maximum score of 10 (100%) and the average evaluation after the primary nursing practice model was 92.43%. This increase can be assumed to be the result of the primary nursing practice model approach that emphasizes holistic care and individual responsibility in providing health services. Based on these results, we recommend the implementation of the primary nursing practice model in patient care, because it has an impact on improving the quality and safety of patients in nursing services in hospitals, so that continuous clinical leadership training is needed for primary nurses in addition to increasing the level of formal education for nurses who are still diploma holders.